Uncorking the Central Bottleneck: Even Novel Tasks Can Be Performed Automatically. - Lyphout-Spitz, Morgan; Maquestiaux, François; Ruthruff, Eric; Chaloyard, Steeven (Journal of Experimental Psychology. Human Perception & Performance, 2024)
Can people perform two novel tasks in parallel? Available evidence and prevailing theories overwhelmingly indicate that the answer is no, due to stubborn capacity limitations in central stages (e.g., a central bottleneck). Here we propose a new hypothesis, which suggests otherwise: people are capable of fully parallel central processing (i.e., bypassing the central bottleneck), yet often fail to do so, mainly due to preparation neglect. This preparation-neglect hypothesis was evaluated in four dual-task experiments pairing novel tasks (Task 1 and Task 2) using arbitrary stimulus–response mappings. Experiment 1, using a classic psychological refractory period (PRP) procedure, replicated the finding of dozens of previous PRP studies: none of the participants bypassed the bottleneck, instead exhibiting large dual-task interference on Task 2 (445 ms). In Experiment 2, the same dual-task PRP trials were randomly intermixed with single-task trials on Task 2, to boost preparation on that task. Here, nearly half the sample of participants bypassed the central bottleneck, exhibiting small dual-task interference on Task 2 (48 ms). Two additional experiments showed that initial practice does not by itself enable bottleneck bypassing, but boosting preparation of Task 2 (via intermixing single-task trials of Task 2) does. We conclude that, when properly prepared, people are capable of far more dual-task automaticity than was previously believed. Public Significance Statement: This study examined the source of the processing limitations that people generally encounter when attempting to perform two tasks at the same time. We demonstrated that novel tasks, when properly prepared, can be performed entirely automatically (i.e., without recruiting attentional resources), thereby bypassing the processing limitations. This finding of dual-task automaticity is striking given that the tasks were neither particularly easy nor previously trained. The key enabler of dual-task automaticity was not practice but boosting advanced preparation of the to-be-performed tasks.